Report upon the mineral statistics of Newfoundland for the calendar year 1904 [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's, Nfld. : Robinson & Co., 1917)
Tables. Running title: Geological Survey of Newfoundland : report for 1904. Cover title: Report upon exploration and boring operations in the central carboniferous basin near Grand Lake, 1904. Electronic reproduction. Mode of access: Internet. 44